IMPLEMENTASI DA’WAH BI AL LISAN DAN DA’WAH BI AL HAL (Studi Pengembangan majelis ta’lim Asy Syarifah Desa Tambung Kec. Pademawu Kab. Pamekasan) - Rusdi Rusdi; Masykurotus Syarifah (LP2M IAI Miftahul Ulum Pamekasan, 2022)
The essence of Islamic da'wah is an invitation or call in the way of Allah subhanahu wa ta'ala (SWT), for goodness and truth in accordance with the teachings of the Qur'an. This study aims to determine the implementation of da'wah bi al lisan and bi al hal in the Asy Syarifah ta'lim assembly in Tambung Village, Kec. pademawu. Benefits Theoretically is expected to be a benchmark for the development of science, especially in the field of Islamic religious broadcasting. In fact, it is hoped that the congregation will be able to apply all forms of practice both theoretically and practically in everyday life. The da'wah method is a method used by da'i to convey messages, information, knowledge to themselves and others. This means that the message of da'wah is conveyed and implemented in the real life of the congregation. This research uses a qualitative descriptive research type. The main data source for the management and members of the Asy Syarifah ta'lim assembly. Data collection techniques are interviews, observation, and documentation. This qualitative research uses inductive data analysis techniques, builds on certain facts, then analyzes and finally finds a general solution to the problem. After analyzing the data, it was found that the method used by the preacher was (manhaj) iqtibas, which is a process carried out to draw a conclusion (istidlal) to understand and interpret the true nature of da'wah. Da'wah/represents the essence of da'wah, True Islam, Experimental Islam, Historical Islam, or Islam that is lived by experience in society. In the implementation process, the da'wah method carried out by the da'i at the ta'lim assembly consists of three stages, namely: Ta'rif (transference), namely the da'wah stage which aims to bring knowledge and knowledge. change. Ignorance becomes an Islamic view, Takwin (coaching), which is the stage where a person begins to pay more attention to objects with the aim of conveying a state of mind (fikroh) that Islam is starting to give the subject of da'wah an opportunity to do charity and tanfidz (charity), namely steps that provide a point press on an outcome given by Allah SWT the reward for giving impetus to work and where the subject of da'wah was previously transformed into the subject of da'wah.